2002
DOI: 10.1037/0021-843x.111.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Waxing and waning in concert: Dynamic comorbidity of conduct disorder with other disruptive and emotional problems over 17 years among clinic-referred boys.

Abstract: Six waves of structured diagnostic assessments were conducted of 168 clinic-referred 7-to 12-year-olds, over 7 years. Wave-to-wave changes in the number of conduct disorder (CD) behaviors were paralleled by correlated changes in the numbers of symptoms of oppositional defiant disorder (ODD), attentiondeficit/hyperactivity disorder (ADHD), depression, and anxiety. In addition, CD in Wave 1 predicted levels of ODD, ADHD, depression, and anxiety in later waves when initial levels of those symptoms were controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
155
4
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(191 citation statements)
references
References 48 publications
17
155
4
12
Order By: Relevance
“…The prevalence of individual CD symptoms varies widely and the median age-of-onset for CD is 11.6 (0.2). Consistent with prior reports, CD is significantly more prevalent among boys (12.0%) than girls (7.1%), and is associated with low education, marital disruption, and urban residence (Lahey et al, 2002;Lambert et al, 2001;Loeber & Keenen, 1994). In addition, CD is estimated to be significantly more prevalent in the West than in other regions of the country.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of individual CD symptoms varies widely and the median age-of-onset for CD is 11.6 (0.2). Consistent with prior reports, CD is significantly more prevalent among boys (12.0%) than girls (7.1%), and is associated with low education, marital disruption, and urban residence (Lahey et al, 2002;Lambert et al, 2001;Loeber & Keenen, 1994). In addition, CD is estimated to be significantly more prevalent in the West than in other regions of the country.…”
Section: Discussionsupporting
confidence: 79%
“…There also are questions regarding the widely documented comorbidity of CD with other mental disorders (Kim-Cohen et al, 2003;Lahey, Loeber, Burke, Rathouz, & McBurnett, 2002;Lahey, Miller, Gordon, & Riley, 1999;Loeber, Burke et al, 2000;Maughan et al, 2004). Although it is clear that CD is associated with other disorders, little is known about whether comorbid disorders precede or follow the onset of CD, whether comorbidities differ by CD subtype, or whether CD is associated with the adult persistence of comorbid disorders.…”
mentioning
confidence: 99%
“…According to this theory, factors such as peer rejection, school failure, and social isolation develop as secondary consequences of aggressive and antisocial behavior (Keiley, Lofthouse, Bates, Dodge, & Pettit, 2003). In a longitudinal study of clinic referred boys, initially high levels of CD predicted increases in depression at later assessments, even when controlling for initial levels of depression (Lahey, Loeber, Burke, Rathouz, & McBurnett, 2002). In contrast, initially high levels of depression did not predict later increases in CD symptoms.…”
mentioning
confidence: 74%
“…Longitudinal research has also indicated that comorbid symptoms both within and across the externalizing and internalizing spectra tend to covary over time. That is, increases in depression tend to occur with increases in CD, and not necessarily before or after such increases (Lahey et al, 2002). Whether these covarying changes derive from common biological mechanisms or environmental influences remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…These correlates include deficient social problem-solving skills and impaired social functioning (Frankel and Feinberg 2002;Matthys et al 1999), poor academic achievement Rapport et al 1999), and co-occurring internalizing disorders Jensen et al 2001). In addition, ADHD and ODD are related prospectively to substance use, poor academic achievement, conduct disorder (CD), and antisocial behavior (Masten et al 2005;van Bokhoven et al 2005), though the association between ADHD and CD may be accounted for by co-occurring ODD (Lahey et al 2002;van Lier et al 2007). …”
Section: Introductionmentioning
confidence: 99%